Say my name? Anonymity or not in elite interviewing - Ellersgaard, Christoph Houman; Ditlevsen, Kia; Larsen, Anton Grau (International journal of social research methodology, 2022)
This article discusses anonymizing elite interviewees. Based on our experiences with interviewing professional elites and ultra-elites in different research projects, we describe how the types of conflicts involving analysis and publication change when interviewees are not promised anonymity. We discuss how contextualizing the elite positions of anonymized interviewees becomes increasingly difficult in interviews with persons who hold prestigious positions of authority and are interviewed in their official capacity. Masking interviewees can create conflicts with regard to the researcher's presentation of results, the transparency of the research and the ability of interviewees to talk back. We show how working with non-anonymized interviewees - and even using excerpts from interviews on public radio - can be an option in qualitative research. However, non-anonymized interviews with elites should be considered only in some instances and may seriously hamper the validity of the material in other cases.